Resposta :
Resposta:
23
[tex] \sf{87-[8²×7:(4+1×3)]}[/tex]
[tex] \sf{87 - ( {8}^{2}x7 \div (4 + 3)) }[/tex]
[tex] \sf{87 - ( {8}^{2} x7 \div 7)}[/tex]
[tex] \sf{87 - ( {8}^{2} x1)}[/tex]
[tex] \sf{87 - {8}^{2} }[/tex]
[tex] \sf{87 - 64}[/tex]
[tex]\rightarrow\boxed{\boxed{\sf{23}}}\checkmark[/tex]
Explicação passo-a-passo:
(espero ter colaborado)
Explicação passo-a-passo:
Determine o valor da expressão :
87-[8²×7:(4+1×3)]=
87-[64.7:(4+3)]=
87-[64.7:(7)]=
87-[64.1]=
87-64=
23
Espero ter ajudado ♥️.